Early childhood caries: Exploring the ethical implications for dental neglect in South Africa - Rampersad, Nashna; Mohamed, Nadia (Health SA = SA Gesondheid, 2025)
Background: Dental neglect is defined as the ‘wilful’ failure of a parent and/or guardian to provide optimal oral healthcare, leading to pain and infection. Child abuse and neglect, including dental neglect, are significant public health issues with long-term consequences for victims. Aim: Given the early childhood caries (ECC) prevalence and socio-economic circumstances of South Africa’s (SA) population, the aim of this review is to explore whether ECC constitutes child neglect in SA. Method: This study explored existing literature on ECC prevalence in SA and its association with dental neglect. It examined SA’s child protection policies and considered the socio-economic context contributing to dental neglect. Results: Evidence suggests that dental neglect, including untreated caries, may indicate broader neglect. However, SA’s historical injustices, poverty, unemployment and lack of access to quality healthcare and education have resulted in high economic disparity among its population, perpetuating ill-health. Early childhood caries in SA is a broader social problem shaped by political, social and economic forces. Societal neglect shifts focus away from parents and towards examination of harmful government policies and actions which impose constraints on families, leading to diseases such as ECC. Conclusion: Child safety, optimum healthcare and prevention of neglect should be priorities of SA’s health and government systems as the country works towards universal health coverage and health system reform. Contribution: This study raises awareness about dental neglect as a child health issue, addresses the root causes of ECC within a societal context, advocates for policy changes and aligns with national and global health priorities.